2023
DOI: 10.1177/20563051231192972
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Evolving Online Learning Landscape: The Case of Science and Religion

Will Marler,
Eszter Hargittai

Abstract: As the online learning landscape expands and social media continue to be an important information source for many, it is important to ask how people evaluate and experience online sources of learning differently and how this compares across domains. Drawing on interviews with 45 adults in the United States, we examine how people’s attitudes and experiences around online learning differ across science and religion. We find that the topic shapes how people evaluate different ways of seeking knowledge online, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Additionally, once ICTs are adopted, older adults may also feel a reliance on family members to help them with further education and any technical support issues (Quan‐Haase et al, 2016; Selwyn, 2004; Selwyn et al, 2003). While this support typically comes from more technologically savvy family members, such as children and grandchildren (Francis et al, 2018), digital assistance can also come from in‐home partner support (Marler & Hargittai, 2022). Hänninen et al (2021) found that older adults often benefit from having access to warm experts who can be “involved in the digital everyday life of older adults, ranging from small acts of motivation and giving practical advice to actual co‐use and proxy use of ICTs” (p. 1596).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, once ICTs are adopted, older adults may also feel a reliance on family members to help them with further education and any technical support issues (Quan‐Haase et al, 2016; Selwyn, 2004; Selwyn et al, 2003). While this support typically comes from more technologically savvy family members, such as children and grandchildren (Francis et al, 2018), digital assistance can also come from in‐home partner support (Marler & Hargittai, 2022). Hänninen et al (2021) found that older adults often benefit from having access to warm experts who can be “involved in the digital everyday life of older adults, ranging from small acts of motivation and giving practical advice to actual co‐use and proxy use of ICTs” (p. 1596).…”
Section: Introductionmentioning
confidence: 99%